2004
DOI: 10.1590/s1679-87592004000200004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the benthic environment of a coastal area adjacent to an oil refinery, Todos os Santos Bay (NE-Brazil)

Abstract: In order to determine the sedimentological and physico-chemical characteristics of the benthic environment and also the level, distribution and probable sources of aliphatic and polycyclic aromatic hydrocarbons, sediment samples were collected at 28 stations in the northeast portion of Todos os Santos Bay. The centre and the east region of the study area showed characteristics of depositional environments with the predominance of silt and clay and high percentages of TOC, nitrogen and sulphur. The molar C/N ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
3
20
3
3
Order By: Relevance
“…The same was found in the studies of Reference [31]. This variability in the C/N ratio is common in sheltered coastal environments with shallow depths, leading to the mixed nature of the organic matter [42].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The same was found in the studies of Reference [31]. This variability in the C/N ratio is common in sheltered coastal environments with shallow depths, leading to the mixed nature of the organic matter [42].…”
Section: Discussionsupporting
confidence: 81%
“…Reference [33] observed a mean C/S ratio of 1.86 in the Santos Estuary (São Paulo State, Brazil) with a minimum of 0.09 in this estuary main channel indicating a strong reduction (anoxic) characteristic in the internal portion of the estuary where there is a larger amount of pelitic sediments and the presence of an important industrial pole. Reference [46] states that one of the sources of sulphur to marine environments is from anthropogenic nature, represented by the petroleum impact.Reference [31] also obtained, for the study area, results which indicate a high degree of anthropogenic contribution related to the residues of degraded petroleum. These authors observed still, very high contents of non-degraded petroleum (the highest of this study) in the sediments adjacent to the RLAM (stations 3, 4 and 6) which may have reflected on the high values of the C/P and N/P ratios presented by these stations in the summer of 2005.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Organic carbon content of sediment can be used as an indicator of pollution. Contamination concentrated at sediment will firstly and mostly affect benthic organisms that are living dependent on the sea bottom (Shine & Wallace, 2000;Venturini et al, 2004;Hyland et al, 2005). Macrofaunal communities and associated environmental variables, such as organic carbon of sediment, are important tools for detecting the health of coastal marine ecosystems (Magni, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The soft-bottom polychaete fauna may represent up to 70% of the total abundance and biomass in an ecosystem (GRAY, 1974), and polychaetes are extensively used as a key taxon in bioenvironmental studies to assess natural and humaninduced changes (POCKLINGTON;WELLS, 1992;JONES;KALY, 1996;PIRES, 2000;GRAY et al, 2002;FARACO;LANA, 2003;VENTURINI et al, 2004).…”
Section: Introductionmentioning
confidence: 99%